Climate, change adaptation assets and group-based approaches: Gendered perceptions from Bangladesh, Ethiopia, Mali, and Kenya - Aberman, Noora-Lisa; Ali, Snigdha; Behrman, Julia A.; Bryan, Elizabeth; Davis, Peter; Donnelly, Aiveen; Gathaara, Violet; Koné, Daouda; Nganga, Teresiah; Ngugi, Jane; Okoba, Barrack; Roncoli, Carla (International Food Policy Research Institute, 2015)
Using a participatory rural appraisal approach, a series of qualitative studies were conducted in four countries facing negative impacts of climate change—Bangladesh, Ethiopia, Kenya and Mali—in order to determine men’s and women’s perceptions of climate change, adaptive approaches, and the degree to which assets and group participation play a role in adaptation strategies. Similarities were found across countries in terms of perceptions of climate change, impacts, and strategies for adaptation. Farmers and pastoralists, groups heavily dependent on natural resources, are starkly aware of and impacted by subtle climatic changes, and those with a stronger asset base were better able to adapt to changes and shocks.